Bilayer structured supramolecular light harvesting arrays based on zinc porphyrin coordination polymers for enhanced photocurrent generation in dye sensitized solar cells. Issue 41 (22nd September 2016) - Zhang, Jun-Xiang; Wu, Yu; Liu, Jia-Cheng; Li, Ren-Zhi
Abstract : Coordination polymers based on an acylhydrazone zinc porphyrin were synthesized and applied in dye sensitized solar cells for enhanced photocurrent generation. Abstract : An acylhydrazone zinc porphyrinP1 and its coordination polymers (CPs, denoted asP1M, M = Mn, Co, Ni, Cu, Zn) with different metal ions (Mn 2+, Co 2+, Ni 2+, Cu 2+ and Zn 2+ ) were synthesized. Then these coordination polymers were assembled into bilayer structured supramolecular chromophores through axially coordinating with anchoring porphyrinAP, and their performance in dye sensitized solar cells was investigated. Our results reveal that the bilayer structured supramolecular chromophore based solar cells show significantly improved photocurrent conversion efficiency. Particularly, P1Mn andP1Zn based solar cells showed a relatively higher short circuit current density ( J SC ) due to their broad absorption bands and remarkable light harvesting abilities. Meanwhile, the V OC values of the cells fabricated with the bilayered chromophores slightly decreased. Electrochemical impedance spectroscopy (EIS) in combination with charge extraction (CE) and transient photovoltage decay (TPD) measurements indicates that the decreased V OC resulted from the vigorous electron recombination and the downward shifted conduction band edge ( E CB ) of titania.